Utilization of Plastic Waste in Making Plastic Bricks as an Effort for Community Development and Creative Economy in Sidodadi Village, Batang Kuis District - Rohani Ganie, Rohani Ganie; Hanafiah, Diana Sofia; Samosir, Zurni Zahara (Talenta Publisher, 2021)
The waste problem in Indonesia is still a problem that has not been resolved until now. The increase in population will also be accompanied by an increase in the volume of waste from human activities. The problem of plastic waste has become common, especially in big cities, suburbs and rural areas. Efforts to recycle plastic waste have been continuously carried out, especially for rural communities, but village communities often underestimate the recycling of plastic waste. This is due to the lack of counseling and guidance on independent and creative businesses and efforts to recycle plastic waste into useful products. One of the efforts to recycle plastic waste is to make bricks which raw material comes from plastic waste. In the process of making plastic bricks, there is a burning process, but this will not cause environmental pollution. Sidodadi Village located in Batang Kuis, Deli Serdang, is an area that has the potential to grow fast. Therefore, the development of Sidodadi Village in the social and economic aspects can be done by developing creative industries. To follow up on this effort, the USU community service team offers a teaching program on making bricks from plastic which can be used as a product of creative industry businesses with various advantages, including to reduce air pollution and environmental pollution.